Impacts of human activities on the spatial distribution and sources of polychlorinated naphthalenes in the middle and lower reaches of the Yellow River. (June 2017) - Li, Qilu; Cheng, Xianghui; Wang, Yan; Cheng, Zhineng; Guo, Liya; Li, Kechang; Su, Xianfa; Sun, Jianhui; Li, Jun; Zhang, Gan
Abstract: The concentrations and compositions of polychlorinated naphthalenes (PCNs) in sediments and suspended particulate matters (SPM) in the middle and lower reaches of the Yellow River were investigated. The mean concentrations of PCNs were 7.15 ± 19.3 ng/g dw in the sediment and 38.1 ± 58.4 ng/g dw in SPM. Tri- and tetra-CNs were the dominant homologue groups in most samples. CN-23 was the predominant congener at all sites, and its presence may be attributed to coal combustion. Combustion indicators showed that local combustion source was the main contributor to the PCN concentrations. These sources were related to the energy structure of this region, where coal is the most important energy resource. Human activities, including industrial thermal processes and reservoir construction, were major factors affecting PCN levels and hydrological conditions, which strongly influenced the environmental fate of PCNs in the Yellow River. Highlights: Study on the behavior of PCNs in the SPM in the middle and lower reaches of the Yellow River were scarce. PCNs mainly accumulated on the SPM, in particular in samples near the reservoir. High proportion of CN-23 may originate from coal burning. Industrial processes and reservoir construction may influence the PCN distribution.